Pulsed DC reactive magnetron sputtering of vanadium dioxide thermochromic thin films - Batista, C. (2011)
Vanadium oxides are an important class of materials with a large diversity of physical and chemical properties which derive from a range of single or mixed valences and a large variety of structures. They are already being used in many technological applications such as electrical and optical switching devices, light detectors, temperature sensors, etc. There has been a great interest in a particular phase, VO2(M), due to its thermochromic behaviour near room temperature which allows the development of smart windows with active control of the solar spectrum, for energy efficiency purposes. However, stoichiometric VO2 is difficult to deposit because of a narrow stability range due to the complex vanadium–oxygen reactive system. In this work, vanadium oxide thin films were synthesised on glass substrates by reactive pulsed direct current magnetron sputtering from a vanadium metal target in an O2/Ar atmosphere. Different processing conditions have been chosen in order to evaluate their influence on the crystal phases formed, surface morphologies and thicknesses and optical performance. The films were characterised by X-ray diffractometry in order to examine the crystal structure and identify the phases present in different films. The obtained VO2(M) films were thereafter analysed in terms of surface morphology by scanning electron microscopy and the characteristic reversible semiconductor-metal transition of the VO2 films was evaluate by optical spectrophotometry in the ultraviolet-visible-near infrared.